Evaluation of Acute and Sub Chronic Toxicity Studies of Siddha Polyherbal Formulation, Thippili chooranam in Wistar Albino Rats - Dr. S. Shankar; Dr. K. S. Uma; Dr. M. Ravichandiran; Dr. N. Kabilan; Dr. P. Amutha (Galore International Journal of Health Sciences and Research, 2026)
Back ground: Herbal drugs were considered safe for a long time. But as science advances the toxicity of herbal drugs had been pronounced. Toxicity analysis is now mandatory for all herbal drugs even they are considered safe. In this regard, Thippili Chooranam a poly herbal formulation indicated for Iya eraippu noi – Bronchial Asthma in siddha system is analyzed for its toxicity. Aim and Objectives: To evaluate the safety of Thippili Chooranam in animal model through screening Acute and Sub chronic toxicity as per OECD guidelines. Standard Operating Procedure: All the ingredients were purified and ground well to prepare Thippili Chooranam. Acute toxicity study was done as per OECD 423 guidelines. Single Oral dose of Thippili Chooranam 2000mg/kg body weight was given to six female Wistar rats and observed for 14 days. On the 15th day they were euthanized and analyzed for toxicity. Sub chronic or 90 days oral toxicity study had been executed as per the OECD 408 guidelines. 20 Wistar rats (10 male and 10 female) of three groups were taken for study. Group I served as control Group II is low dose (200mg/kg b.w.) and Group III is moderate dose (400 mg /kg body weight). On 91st day All were sacrificed and biochemical histopathological examination were done. Results and Discussion: The histopathological analysis of Thippili Chooranam reveals, no remarkable toxicity of the drug and this drug is having a high safety in chronic use. Keywords: Siddha poly herbal formulation, Thippili chooranam, toxicity studies, Thippili Iya eraippu noi